2013
DOI: 10.1152/ajpheart.00443.2013
|View full text |Cite
|
Sign up to set email alerts
|

Activation of melanocortin receptors in the intermediolateral cell column of the upper thoracic cord elicits tachycardia in the rat

Abstract: Melanocortin receptors (MCRs) are present in the intermediolateral cell column of the spinal cord (IML). We tested the hypothesis that activation of MCRs in the IML elicits cardioacceleratory responses and the source of melanocortins in the IML may be the melanocortin-containing neurons in the hypothalamic arcuate nucleus (ARCN). Experiments were done in urethane-anesthetized, artificially ventilated adult male Wistar rats. Microinjections (50 nl) of α-melanocyte stimulating hormone (α-MSH) (0.4-2 mM) and adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Although the brain areas where MC3/4R exert their effects on the autonomic nervous system and BP regulation are still poorly understood, MC4R are abundant in the paraventricular nucleus of the hypothalamus (PVN) and in brainstem areas involved in autonomic regulation as well as in the intermediolateral medulla (IML) 32,33 . For example, acute stimulation of MC4R in the PVN or IML raises renal SNA and HR, respectively, 32,33 while MC4R located on cholinergic preganglionic parasympathetic and sympathetic neurons appear to contribute, at least in part, to obesity hypertension 34 . However, additional studies are needed to determine the brain regions where the melanocortin system is most important for modulating cardiovascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Although the brain areas where MC3/4R exert their effects on the autonomic nervous system and BP regulation are still poorly understood, MC4R are abundant in the paraventricular nucleus of the hypothalamus (PVN) and in brainstem areas involved in autonomic regulation as well as in the intermediolateral medulla (IML) 32,33 . For example, acute stimulation of MC4R in the PVN or IML raises renal SNA and HR, respectively, 32,33 while MC4R located on cholinergic preganglionic parasympathetic and sympathetic neurons appear to contribute, at least in part, to obesity hypertension 34 . However, additional studies are needed to determine the brain regions where the melanocortin system is most important for modulating cardiovascular function.…”
Section: Discussionmentioning
confidence: 99%
“…MC4R agonists increase blood pressure by targeting cholinergic neurons, including the sympathetic preganglionic neurons of the IML (Sohn et al 2013). In the IML, MC4R neurons also control heart rate (Iwasa et al 2013) (Fig. 4).…”
Section: Mc4r Neuronsmentioning
confidence: 99%
“…On the other hand, an α-MSH-expressing viral vector injected into the NTS increased sympathetic activity and the heart rate and reduced parasympathetic activity in mice [170]. Similarly, Iwasa et al [171] observed an increased heart rate after α-MSH had been microinjected into the IML, the location of cholinergic sympathetic preganglionic neurons. Recent work shows that re-expressing MC4Rs specifically in cholinergic neurons renders MC4R null mice hypertensive without affecting their obesity [32].…”
Section: Role In Blood Pressurementioning
confidence: 99%